An American travesty legal responses to adolescent sexual offending - Zimring, Franklin E. (Chicago, Ill. ; London : University of Chicago Press, 2004)
'An American Travesty' examines the attitude of the American judicial system to juvenile sexual offenders. Too often, it argues, the system treats juveniles as if they were adults & failes to take either age or developmental status into account.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Teenage sex offenders -- Legal status, laws, etc. -- United States; Sex crimes -- United States; Juvenile courts -- United States; True Crime; United States of America, USA; Society & culture: general; Crime & criminology; Juvenile offenders; Criminal law: procedure & offences